Assessing readiness to implement patient navigator programs in Toronto, Canada. Issue 4 (18th October 2021) - Kokorelias, Kristina M.; Gould, Sarah; DasGupta, Tracey; Cass, Dan; Hitzig, Sander L.
Abstract: Objective: To explore factors influencing the implementation of patient navigator programs within a hospital for seniors with complex care needs. Methods: A qualitative descriptive design using in‐depth interviews was conducted. Participant interviews were conducted in Toronto, Ontario between September 2020 and February 2021. Data were analysed using thematic analysis. Results: Thirty‐five semi‐structured interviews were conducted with 38 participants from a large urban hospital (n = 21) and community healthcare organizations (n = 17), including organizational leaders, and acute care and rehabilitation providers. Follow‐up interviews occurred with 16 participants (7 from the community and nine from the hospital). This study identified five key factors influencing organizational readiness for successful implementation of a patient navigator program for seniors with complex conditions, which included: (a) vision from senior leadership, (b) technological infrastructure, (c) existing hospital‐community partnerships, (d) well‐established process for referrals, and (e) staff capacity. The overarching theme of communication was also identified. Conclusions: The findings of this study provide a better understanding of hospital and community professionals' needs and challenges when implementing patient navigator programs for seniors with complex care conditions. There are a number of factors that influence an organization's readiness for program uptake and delivery, with the need for clear communication being paramount. Further research to test the effects of readiness on successful implementation outcomes is warranted.